Critical Incident History Questionnaire Replication: Frequency and Severity of Trauma Exposure Among Officers From Small and Midsize Police Agencies. Issue 2 (21st March 2015) - Chopko, Brian A.; Palmieri, Patrick A.; Adams, Richard E.
Abstract : Frequency and severity of trauma exposure are thought to influence posttraumatic reactions. Weiss et al.'s Critical Incident History Questionnaire (CIHQ; 2010) measures these variables among law enforcement officers; they reported findings using a sample of officers from large urban departments. We noted the need for replication studies utilizing samples from smaller and rural police agencies. The purpose of this study was to replicate the CIHQ findings from Weiss et al. using a sample ( N = 193) of officers from small and midsize police departments and officers whose duties include policing rural and isolated jurisdictions. Frequency and severity findings were similar to those reported by Weiss et al. (2010). Regarding frequency, the present study found the critical incident exposure mean score was 188.5, compared to 168.5 from Weiss et al. (2010). Making a mistake that kills or injures a colleague had the highest mean nomothetic severity rating in both studies. Among the various variables examined in this study, PTSD symptoms demonstrated the strongest association with the exposure indices, based on Spearman rank correlations ( r = .26–.46).